Audições orquestrais para flauta no Brasil: um estudo sobre estratégias de preparação - Juliana Maria Bonfim Rodrigues (2015)
The success of a flutist in an orchestral audition is closely related to an effective preparation. This process involves comprehension of the requested repertoire for the audition and the formulation of practice strategies. This research aims to discuss the main items evaluated in the three most requested orchestral excerpts in Brazil between 2009 and 2014 (Dreams of a Summer Night, Scherzo - Mendelssohn, Prélude à l'après-mid d'un Faune - Debussy and Daphnis et Chloe - Ravel) and describes the strategies adopted by flutists of Brazilian orchestras comparing to the preparation process of an athlete for a competition. A semi open questionnaire was answered by ten flutists of four important Brazilian orchestras. The answers allowed collecting and analyzing information about the strategies used by these flutists during the run-up to an orchestral audition and their comments on each of the three orchestral excerpts. It w as observed that the preparation strategies of different flutists were similar to each other and to methods applied by athletes in preparation for a competition. The most relevant characteristic s presented by the interviewed flutists were analyzed in each orchestral excerpt.